Loss of Coral Trait Diversity and Impacts on Reef Fish Assemblages on Recovering Reefs - Lintao Huang; Mike McWilliam; Chengyue Liu; Xiaolei Yu; Lei Jiang; Chen Zhang; Yong Luo; Jianhui Yang; Xiangcheng Yuan; Jiansheng Lian; Hui Huang (Ecology and Evolution, 2024)
ABSTRACT Understanding patterns of biodiversity change is essential as coral reefs experience recurrent cycles of disturbance and recovery. Shifts in the total cover and species composition of habitat‐forming corals can have far‐reaching consequences, including shifts in coral functional traits and impacts on local fish assemblages. We surveyed coral and fish assemblages along the southern coast of Hainan Island near Sanya, China, in 2006, 2010, and 2018, during a period with repeated mass bleaching events. We showed that coral biodiversity in this region is in a state of flux, with losses and gains in coral cover and an increase in species richness over time. Despite increasing species diversity, the region suffered a loss of coral trait diversity by 2010, with an incomplete recovery by 2018, owing to declines in species with key habitat‐forming traits (e.g., high surface areas and fractal structure) such as corymbose corals. Concurrently, there was an increase in functional redundancy due to the proliferation of the dominant encrusting and massive corals. Coral cover was positively associated with the abundance of reef fish, indicating that the changes observed in coral abundance can impact reef‐associated species. These results demonstrate that the slow recovery of coral biodiversity in southern Hainan Island has been hampered by the loss of specific coral traits and highlight the importance of protecting vulnerable coral traits in conservation and management strategies.